Enhancement of Cytotoxicity and Apoptosis Induction of Doxorubicin by Brazilein Containing Fraction of Secang (Caesalpinia sappan L.) on T47D Cells - Rohmad Yudi Utomo; Annisa Novarina; Prisnu Tirtanirmala; Ria Fajarwati Kastian; Riris Istighfari Jenie (Indonesian Society for Cancer Chemoprevention, 2018)
Combination chemotherapy (co-chemotherapy) is a recent strategy to reduce the toxicity effect and increase the effectivity of chemotherapeutic agent, such as Doxorubicin (Dox). Caesalpinia sappan L. are potential to be developed as co-chemoterapeutic agents due to its strong cytotoxicity toward several breast cancer cells. The purpose of this research is to observe the cytotoxicity of Brazilein containing fraction (BCF) in single and its combination with doxorubicin on T47D cells. BCF was obtained by fractionation using chloroform:ethyl acetate (40:60 v/v) as mobile phase. Molecular docking results showed that Brazilein and Brazilin interacted with Bcl-2 with different binding properties. Based on MTT assay, Dox and BCF performed potent cytotoxicity with IC50 value of 403 nM and 68 μg/mL, respectively. BCF increased the cytotoxicity of Dox and performed synergism with CI value <1 and decreased possible toxicity with DRI value>1. Under Annexin V PI staining Flowcytometry, BCF in single and its combination with doxorubicin induced apoptosis. In conclusion, single treatment of BCF and its combination with Dox performed cytotoxic effect and induced apoptosis on T47D cell lines.Keywords: Brazilein containing fraction, Doxorubicin, Co-chemoteraphy, Apoptosis, T47D cells